Analysis of contract ED-LP16-01 for the supply of food for the PAE program in the department of Santander (2023)
Government procurement in Colombia is definitely one of the fundamental tools to achieve the objectives set out in each of the government plans of the central and departmental level that the incoming governors establish to develop during the time they were elected. We cannot hide that there are many benefits of this tool, but there are also countless cases in which the fundamental principles of public procurement have been put into question, the respective control entities put the magnifying glass and study each of the contractual processes carried out by the territorial entities that may have indications of possible acts of corruption, the generation of these projects has as its main function to remedy unmet needs for the community but more regularly than you think this main objective becomes the benefit of a few. This essay seeks to address the School Feeding Program PAE from where it was born and why it was created, as well as to know the regulations governing these processes. Taking as a case study the one that occurred in the department of Santander in the contract 601 of 2016, contract signed between the territorial entity Gobernación de Santander represented by Didier Tavera and the cooperative Multiactiva Surcolombiana de Inversiones Limitada, on the other hand, the consequences of corruption go beyond illicit enrichment, prevarication, influence peddling, among others if not also the great consequences are suffered directly by the target population of this feeding program and includes all student population and in all latitudes of the department of Santander.